2016
DOI: 10.1371/journal.pone.0164685
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Mapping of Anopheles darlingi Densities in a Residual Malaria Transmission Area of French Guiana by Using Remote Sensing and Meteorological Data

Abstract: Local variation in the density of Anopheles mosquitoes and the risk of exposure to bites are essential to explain the spatial and temporal heterogeneities in the transmission of malaria. Vector distribution is driven by environmental factors. Based on variables derived from satellite imagery and meteorological observations, this study aimed to dynamically model and map the densities of Anopheles darlingi in the municipality of Saint-Georges de l’Oyapock (French Guiana). Longitudinal sampling sessions of An. da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…Two main approaches are used to understand and predict mosquito population dynamics: i) process-based (or mechanistic) models describing biological knowledge within a mathematical or computational framework, and ii) empirical (or statistical) models, which try to find, from the observed data, a predictive function of the response variable (mosquito populations) based on a set of predictors within a statistical or a machine learning framework. Both approaches have been successfully applied to different mosquito species and geographical contexts [5][6][7][8][9][10][11][12][13][14][15][16][17], resulting in a better understanding of their distribution [5-8, 11, 12, 16] and dynamics [9,10,13,17,18] and the assessment of different mosquito control strategies [19,20]. However, most case studies only develop one of the two approaches (either empirical [5-8, 11, 12, 14, 16] or process-based [9,10,13,15,17] depending on the availability of data and knowledge), and do not compare the capacity of the two approaches to predict mosquito population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Two main approaches are used to understand and predict mosquito population dynamics: i) process-based (or mechanistic) models describing biological knowledge within a mathematical or computational framework, and ii) empirical (or statistical) models, which try to find, from the observed data, a predictive function of the response variable (mosquito populations) based on a set of predictors within a statistical or a machine learning framework. Both approaches have been successfully applied to different mosquito species and geographical contexts [5][6][7][8][9][10][11][12][13][14][15][16][17], resulting in a better understanding of their distribution [5-8, 11, 12, 16] and dynamics [9,10,13,17,18] and the assessment of different mosquito control strategies [19,20]. However, most case studies only develop one of the two approaches (either empirical [5-8, 11, 12, 14, 16] or process-based [9,10,13,15,17] depending on the availability of data and knowledge), and do not compare the capacity of the two approaches to predict mosquito population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In the study region, temperatures are usually not considered as a good predictor of malaria vector presence and density as it oscillates in the ideal range of values for the mosquito development all the time, and present diurnal variations that exceed the seasonal ones [29]. However, past studies demonstrated significant positive correlations between precipitations and Anopheles darlingi abundance [12,30]. Thus, we can expect significant relationships between precipitations and malaria cases.…”
Section: Discussionmentioning
confidence: 92%
“…Present and past studies show the influence of vector dynamics on malaria transmission [12,28]. In 2017, the heaviest rainfall hit the area since 2000; it may have had an impact on the productivity of vector breeding sites in the transitional period between the wet and the dry season, and the abundance of An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anopheles adult female mosquitoes were selected from field mosquito collections done in 6 distinct sites from French Guiana, during entomological surveys, using different collection methods, over different sampling periods (Figure 1) [3,3941]. After collections, mosquitoes were sorted by genera and Anopheles mosquitoes were morphologically identified under a binocular loupe at a magnification of ×56 (Leica M80, Leica, Nanterre, France) using standard taxonomic keys for the region (Floch and Abonnenc 1951, Forattini 1962, Faran and Linthicum 1981).…”
Section: Methodsmentioning
confidence: 99%